Linear equalization techniques for hybrid systems in the millimeter wave band of communications - Barb, Gordana-Raluca (2018)
Wireless communications are continuously evolving, and the demand for higher data rates, more capacity, a better quality of service and more coverage is rising. The next generation, 5G, is currently being developed and it is expected to be delivered by 2020. However, in order to fulﬁll the 5G requirements, such as a consistent user experience, peak bit rates of 10 to 50 Gbps, higher reliability and availability, changes in the cellular architecture are needed, using new technology. Millimeter waves are a promising carrier frequency for 5G cellular systems, due to their underutilized large bandwidth that can potentially provide high data rates for future wireless networks. Single-carrier frequency-division multiple access (SC-FDMA), a modiﬁed form of orthogonal frequency-division multiple access (OFDMA), is a promising solution technique for high data rate uplink communications in future cellular systems. When compared with OFDMA, SC-FDMA has similar throughput and essentially the same overall complexity. A principal advantage of SC-FDMA is the peak-to-average power ratio (PAPR), which is lower than that of OFDMA, being less sensitive to nonlinear distortion caused by the power ampliﬁer (PA). It is well known that an eﬃcient PA is critical for future millimeter wave based wireless systems. Conjugating mmWaves with massive MIMO will allow packing a higher number of antennas into the same volume, since mmWaves have a smaller wavelength than the currently used cellular systems. Consequently, millimeter wave communications and massive MIMO have been considered as two of the key enabling technologies needed to provide multi-Gbps for future wireless communications. In this Dissertation a hybrid analog-digital multi-user linear equalizer for broadband mmWave massive MIMO SC-FDMA systems is designed and evaluated. The digital part is computed on a per subcarrier basis and the analog part is constant over all subcarriers. The simulation results show that the proposed hybrid equalizer achieves an average BER close to the full-digital equalizer (gap of ∼ 1 dB), when the number of RF chains is twice the number of users. When the number of RF chains is smaller than twice the number of users, a compromise between complexity and performance is achieved.